Global Existence and Asymptotic Behavior of Solutions for the Cauchy Problem of a Dissipative Boussinesq-Type Equation - Esfahani, Amin; Mohammadi, Hamideh B. (Mathematical Modelling and Analysis, 2017)
We consider the Cauchy problem for a Boussinesq-type equation modeling bidirectional surface waves in a convecting fluid. Under small condition on the initial value, the existence and asymptotic behavior of global solutions in some time weighted spaces are established by the contraction mapping principle.